Characteristics of Patient with Brachial Plexus Injury in Neurophysiology Laboratory of Dr. Hasan Sadikin General Hospital Bandung, Indonesia, from 2003 to 2012 - Ivan Kurnianto; Nani Kurniani; Arifin Soenggono (Althea Medical Journal, 2015)
Background: Brachial plexus is a network of nerves that controls the upper limb. Unfortunately, it can be injured easily which is called brachial plexus injury (BPI). It can cause disability. Until now, the epidemiology of BPI in Indonesia is still lacking. The aim of this study was to describe the characteristics of patients with BPI in Bandung, in order to increase knowledge and attention of health care provider and community to prevent BPI.Methods: This was a descriptive retrospective study. Data from medical records of patients with BPI who underwent electromyography (EMG) in Neurophysiology Laboratory Dr. Hasan Sadikin General Hospital, Bandung from 2003 to 2012 were collected. The data included age, sex, mode of injury, affected side and distribution of paralysis. Collected data were presented as percentages shown in tables.Results:  A total of 91 cases were collected during study period, which consisted of 69 males and 22 females (76% vs. 24%). Most of them were in productive age group (11−20 years and 21−30 years). The main cause of brachial plexus injury was traffic accident (76%), followed by birth injury. Distribution of paralysis was mostly in postganglionic area of cervical (C)5, C6, C7, C8 and thoracal (T)1 (67%). Around two third of the cases involved the right side of upper limb.Conclusions: The study showed that most of patients with BPI are male in their productive ages. Traffic accident is the most common cause, and the most affected side is the right side of upper limb. DOI: 10.15850/amj.v2n3.529